Malay syllables recognition using dynamic time warping - 295944 Cheah, Eng Liang (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Computer)) - Universiti Teknologi Malaysia, 2001